Faktor-Faktor yang Berhubungan dengan Terkontrolnya Tekanan Darah pada Hipertensi Primer - I Made Sukarja (Jurnal Gema Keperawatan, 2015)
This research was observational analysis with case control approach using purposive sampling technique. The sample collected was 134 respondents consist of 67 cases and 67 controls. Effect of independent and the dependent variable in this research conducted with chi squre test and multiple logistic regression. The results of this research indicated that there is a association between nutritional status (OR=5.167), low salt diet (OR=21.147), antihypertensive medication adherence (OR=11.659), and physical activity (OR=5.273) with controlled blood pressure (p=0.000). On the other hand, the variable smoking habit (p=0.070, OR=0.863) and stress level (p=0,863, OR=1.127). The most dominant variable was the lowsalt diet. Based on multivariate analysis was also obtained by the equation Y= -5.315+ 2.326X1+2.756X2+2,225X3+2,585X4. The probability of achieving controlled blood pressure in hypertensive patients without four factors above is 0.5%.